2018
DOI: 10.1371/journal.pone.0209294
|View full text |Cite
|
Sign up to set email alerts
|

L1 Cell Adhesion Molecule (L1CAM) expression in endometrioid endometrial carcinomas: A possible pre-operative surrogate of lymph vascular space invasion

Abstract: BackgroundRisk stratification of endometrial carcinomas is primarily based on surgical staging that requires extensive retroperitoneal lymph node dissection. One of the most powerful predictor of lymph node involvement is the lymph vascular space invasion (LVSI). The objective of this study was to determine the potential of L1 Cell Adhesion Molecule (L1CAM) to predict LVSI and its association with other risk factors in endometrioid endometrial carcinomas.Materials and methodsWe studied 47 consecutive patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 29 publications
3
8
0
Order By: Relevance
“…Patients with L1CAM high expression had unfavorable OS in comparison with the one with L1CAM low expression. These data are in line with previously published prognostic data on L1CAM expression in other human malignancies, such as NSCLC, 5 gastric cancer, 10 colorectal cancer, 4 , 23 endometrial carcinoma, 9 and glioblastoma. 7 , 13 In addition, the Human Protein Atlas database ( https://www.proteinatlas.org/ ) has also indicated that L1CAM is a prognostic marker.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Patients with L1CAM high expression had unfavorable OS in comparison with the one with L1CAM low expression. These data are in line with previously published prognostic data on L1CAM expression in other human malignancies, such as NSCLC, 5 gastric cancer, 10 colorectal cancer, 4 , 23 endometrial carcinoma, 9 and glioblastoma. 7 , 13 In addition, the Human Protein Atlas database ( https://www.proteinatlas.org/ ) has also indicated that L1CAM is a prognostic marker.…”
Section: Discussionsupporting
confidence: 91%
“… 4 In the past few years, a host of research have been carried out around the world to discuss the expression and function of L1CAM in human malignancies of different patient samples. 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 It has been demonstrated as a predictive factor of poor prognosis in Non-Small Cell Lung Cancer (NSCLC), cervical cancer, endometrial cancer, gastric cancer, glioma, renal cell cancer, ovarian carcinoma, melanoma, colon cancer, and pancreatic cancer. In addition, previous studies have also indicated the involvement of L1CAM in the tumor cell invasion, metastasis, and chemoresistance.…”
Section: Introductionmentioning
confidence: 99%
“…Our data indicate that preoperative L1CAM assessment using percentage assessment is not helpful in decision making regarding lymphadenectomy. Nevertheless, our data confirm previously demonstrated associations of L1CAM expression and other high-risk features such as FIGO stage [30], tumour grade [30][31][32], histological subtypes [30,31], LVSI [21,30,33], and ER and PR status [34]. We showed that L1CAM is a robust marker that indicates patients at higher risk for distant relapse.…”
Section: Discussionsupporting
confidence: 91%
“…In a previous study with 47 consecutive patients who had complete surgical staging, we found LVSI in 63.4% of cases, and L1CAM positivity in 17% of the cases. All L1CAM-positive cases had LVSI, suggesting a potential role of this molecule at the time of diagnostic biopsy, particularly in identifying patients in whom lymphadenectomy is crucial [24].…”
Section: Discussionmentioning
confidence: 98%